2010
DOI: 10.1525/jer.2010.5.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Views of Involvement in Concurrent Research with Their Neonates

Abstract: It would be useful to researchers and bioethicists to know more about parents’ decision processes and emotional state during the time they are deciding whether to enroll their infant in a clinical trial. The aim of this research study was to discover whether parents who had been previously asked to enroll their neonates in clinical trials would have found concurrent research about their decision-making overly burdensome. Twenty-seven parents of critically ill neonates who had been approached for their child’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…of the perspectives of parents during their actual experience, as their accounts may be influenced by time and the health outcomes of their baby (34). The women were approached for informed consent of the original RCT shortly before giving birth to a preterm infant and sometimes when they were already in labour.…”
Section: Accepted Articlementioning
confidence: 99%
“…of the perspectives of parents during their actual experience, as their accounts may be influenced by time and the health outcomes of their baby (34). The women were approached for informed consent of the original RCT shortly before giving birth to a preterm infant and sometimes when they were already in labour.…”
Section: Accepted Articlementioning
confidence: 99%
“…Do caregivers have their children participate for their own personal reasons, or to benefit their children (Warin, 2011)? A great deal of research that covers this issue is relevant largely to clinical populations (e.g., Ward, 2010), such that the caregivers' motivation to participate is largely driven by a possible medical benefit to their child. In some clinical research, caregivers indicated that they participated because they wanted better healthcare options for their child and they wanted to help other children (e.g., Fisher, McKevitt, & Boaz, 2011).…”
Section: Caregiver Motivation For Participationmentioning
confidence: 99%
“…In some clinical research, caregivers indicated that they participated because they wanted better healthcare options for their child and they wanted to help other children (e.g., Fisher, McKevitt, & Boaz, 2011). Caregivers of terminally ill infants who chose to include their children in clinical research indicated that they actually gained better understanding of their experiences and obtained more information as a result of their participation (Ward, 2010). Additionally, some caregivers were altruistic in their motivations to participate in research, and just wanted to aid in research findings (e.g., Hayman et al, 2001).…”
Section: Caregiver Motivation For Participationmentioning
confidence: 99%
See 2 more Smart Citations